Tourism in Africa : Harnessing Tourism for Growth and Improved Livelihoods - Christie, Iain; Fernandes, Eneida; Messerli, Hannah; Twining-Ward, Louise (Washington, DC: World Bank and Agence Française de Développement, 2014)
This report is the first to examine tourism in Africa comprehensively and regionally and the first to recommend practical, evidence-based measures enabling the sector s economic and development power. This gives new impetus to the continent s development progress by leveraging tourism in pursuit of lasting poverty alleviation and the creation of significantly more jobs and opportunities for all Africans.